Accretion of galaxy groups into galaxy clusters - Benavides, José A. (2020)
We study the role of group infall in the assembly and dynamics of galaxy clusters in ΛCDM. We select 10 clusters with virial mass M200 ∼1014 M from the cosmological hydrodynamical simulation Illustris and follow their galaxies with stellar mass M⊙ ≥ 1.5 × 108 M. A median of ∼38% of surviving galaxies at z = 0 is accreted as part of groups and did not infall directly from the field, albeit with significant cluster-to-cluster scatter. The evolution of these galaxy associations is quick, with observational signatures of their common origin eroding rapidly in 1-3 Gyr after infall. Substructure plays a dominant role in fostering the conditions for galaxy mergers to happen, even within the cluster environment. Integrated over time, we identify (per cluster) an average of 17 ± 9 mergers that occur in infalling galaxy associations, of which 7 ± 3 occur well within the virial radius of their cluster hosts. The number of mergers shows large dispersion from cluster to cluster, with our most massive system having 42 mergers above our mass cut-off. These mergers, which are typically gas rich for dwarfs and a combination of gas rich and gas poor for M⊙ ∼1011 $m M_odot$, may contribute significantly within ΛCDM to the formation of specific morphologies, such as lenticulars (S0) and blue compact dwarfs in groups and clusters.